Konstruksi Sosial Dan Apresiasi Masyarakat Terhadap Batik Di Kota Jepara - Aan Widiyono; Diah Ayu Mawarti (Universitas Padjadjaran, 2020)
Batik Jepara is a cultural heritage that emerged in the era of R.A. Kartini. This research aims to examine the social construction and appreciation of the Jepara community members towards batik in Jepara City. This research uses a qualitative approach. The subjects of this research are the people of Jepara. The data was collected by using the interview, observation and documentation. The research demonstrates various social constructions of the batik in Jepara. Public figures think that the Jepara batik is a characteristic and identity of Jepara. Academics see and interpret batik Jepara as a local cultural heritage that must be preserved. Students interpret batik as a work of art that must be appreciated. The teachers see Batik Jepara as a tradition and local wisdom. People see Batik Jepara as the identity and pride of Jepara. Entrepreneurs and craftsmen of Batik interpret Batik Jepara as an industry and a source of income. Public appreciation of batik as a fashion in the everyday life has been done in many ways, including preserving, appreciating and respecting the creation of batik. The society strives to respect, and appreciate their own culture, by wearing batik in everyday life as an outfit for formal and non-formal activities.